To what extent does internationalization challenge the national education system of Azerbaijan? - Taghiyev, Ali; Hasanzade, Tofig; Muradaliyeva, Vusala (ADA University, 2023)
The rise of globalization fastened international cooperation among educational institutions which made international education a new phenomenon in the 21st century. Today, we see more and more people are striving to get international education abroad while universities also compete for international talents, grow the number of mobility programs, and develop international programs. However, international education brought some challenges for the national governments, more specifically the education system. In this paper, we aim to analyze the current challenges that development of international education created at the national, institutional, and international level, and propose relevant policy solutions in the context of national education in Azerbaijan.
Keywords: International education -- Azerbaijan; Education and globalization; Educational policy -- Azerbaijan; Public and International Affairs; Public and International Affairs